Speculative markets drug circuits and derivative life in Nigeria - Peterson, Kristin 1966- (Duke University Press, 2014)
Introduction: chemical multitudes : fake drugs and pharmaceutical regulation in Nigeria -- Idumota : pharmacists, traders, and the new free market -- Risky populations : divestment and militarized austerity -- Regulation as a problem of discernment : open markets in the making -- Derivative life : nominalization and the logic of the hustle -- Chemical arbitrage : a social life of bioequivalence -- Marketing new monopolies: intellectual property, debt, and drug geopolitics -- Conclusion: old specters, new dreams
Includes bibliographical references and index. - Description based on print version record
Keywords: Pharmaceutical industry / Nigeria; Free enterprise / Nigeria; Wirtschaftsentwicklung; Pharmazeutische Industrie; Spekulation -- Wirtschaft; Nigeria